Strength of Tubular Members– Numerical Comparison of API RP2A to ISO Codes - Sambu Potty, Narayanan (2010)
Worldwide, currently there are three codes used for offshore jacket platform design i.e. API RP2A WSD, API RP2A LRFD and ISO 19902. Of these, the ISO code is formulated for application all over the world. API RP2A WSD is still being used for jacket platform design, not only in the Gulf of Mexico, but also in most of developing countries.API RP2A LRFD and ISO have introduced limit state design in place of working stress design. The limit state design is followed all over the world for most of the design codes. ISO will introduce environmental load factors for each region, in its appendix. The reliability of jacket platforms is maintained in API RP2A LRFD by setting target safety factor the same as that provided in WSD designs, which means structures designed as per LRFD code will have same reliability as API RP2A WSD (which has already provided safe structures and the best available practice for design). For ISO code, the API RP2A LRFD was based as the base code of design. In this paper, the nine stress equations of the above three codes are compared. The knowledge of the strength equations in the codes is useful for determining resistance factors for code calibration. The resistance formulations are numerically compared and the similarities and differences are determined. The member resistance formulae for local buckling, hydrostatic pressure, interaction formulae for axial compression, bending stress, axial tension and hoop stress introduced in the 6th edition of WSD in 1975, have undergone major changes. In the 11th edition (1980), equations were introduced for allowable hoop stress, a formula for combined effects of axial compression, bending and hydrostatic pressure. When API LRFD version was introduced in 1993, some formulae were modified. Incorporating these, the 21st edition of WSD was published in 2000. ISO 13819 was published in 1998, modified in 2007(ISO 19902). Some provisions in ISO were directly adopted from API RP2A LRFD while others improved and included.